The influence of tax knowledge, tax sanctions and taxpayer awareness on msmes taxpayer compliance (an empirical study on registered msmes at KPP Pratama Sukomanunggal Surabaya City) - Pramudianti, Mira (Cebong Journal, 2023)
Payment and reporting of taxes is an obligation of citizens as a manifestation of the role of citizens in building and financing national development. Taxes that have been collected by the Directorate General of Taxes will be distributed to authorized parties in the country's development process. There are three types of tax collection in Indonesia, namely the official assessment system, self assessment system and withholding assessment system. However, currently most of the tax collection in Indonesia uses a self-assessment system. The self-assessment system is a collection system that authorizes taxpayers to determine the amount of tax payable to be paid, make deposits and report taxes independently. This research includes research that uses the Quantitative Correlational method because this research was conducted to examine the relationship between variables. In the model analysis and hypothesis testing, it can be seen that the calculated F value is equal to and the significant value is 0.000, meaning that the variables of tax knowledge, tax sanctions, taxpayer awareness simultaneously have a significant effect on taxpayer compliance. In the t hypothesis, it is known that the variable knowledge of taxation and sanctions taxation affects taxpayer compliance. Meanwhile, taxpayer awareness affects taxpayer compliance.